النوافذ الإسلامية في البنوك التقليدية ودورها في تعزيز الشمول المالي - خضير, عقبة (جامعة الوادي University of Eloued, 2021)
هدف الدراسة إلى التعرف على دور النوافذ الإسلامية في البنوك التقليدية في تعزيز الشمول المالي من حيث استعراض المفاهيم الأساسية للنوافذ الإسلامية والخدمات التي تقدمها بالإضافة إلى التعرض إلى مفهوم الشمول المالي وأهدافه وأهميته الاقتصادية والاجتماعية في المجتمع. حيث تعتمد الدراسة على المنهج الوصفي التحليلي لدراسة وتحليل الجوانب المختلفة للشمول المالي والنوافذ الإسلامية في البنوك التقليدية، وخلصت الدراسة إلى أن التمويل عن طريق النوافذ الإسلامية يعطي خيارات متعددة خاصة للفئات المحرومة من التمويل في البنوك التقليدية وذلك من الخدمات التي تقدمها النوافذ الإسلامية، فهي تساهم بشكل كبير في انتشار الشمول المالي في المجتمع. The study aims to identify the role of Islamic windows in traditional banks in promoting financial inclusion in terms of reviewing the basic concepts of Islamic windows and the services they provide, in addition to exposure to the concept of financial inclusion, its objectives, and its economic and social importance in society. Where the study relies on the descriptive analytical approach to study and analyze the various aspects of financial inclusion and Islamic windows in traditional banks, and the study concluded that financing through Islamic windows gives multiple options, especially for groups deprived of financing in traditional banks, and that is one of the services provided by Islamic windows. Significant spread of financial inclusion in society.
Les guichets islamiques dans les banques conventionnelles et leur rôle dans la promotion de l'inclusion financière
مقال
Keywords: الشمول المالي، النوافذ الاسلامية، الصيرفة الاسلامية، منتجات مالية، الثقافة المالية; Keywords Financial inclusion, Islamic windows, Islamic banking, financial products, financial culture